Strategic Management: Text and Cases - Lumpkin G. T. (Mc Graw Hill, 2009)
Strategic Management: Text and Cases, Fifth Edition, by the prestigious authors Dess/Lumpkin/Eisner provide solid treatment of traditional topics in strategic management as well as thorough coverage of contemporary topics such as digital & internet strategies, innovation & corporate entrepreneurship, knowledge management, and intellectual assets. The text is rounded off by rich, relevant, and teachable cases. This text’s accessible writing style and wealth of new and updated illustrations, which clarify the most difficult topics, make this text the best resource for your students.